FAITH AND POWER: THE DUAL PATHWAYS OF ISLAMIZATION IN THE EARLY HISTORY OF THE BIMA SULTANATE - Aksa; Hasaruddin; Sabara; Djody Firmansyah (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines the early Islamization of the Bima Sultanate by analyzing the relationship between faith and political power as the principal forces shaping religious and political transformation. It explains how different Islamization networks contributed to the emergence of Islamic rule and identity in Bima. The study employs the historical method through heuristics, source criticism, interpretation, and historiography. It integrates historical, sociological, and Islamic studies perspectives to reconstruct the Islamization process within its broader political and cultural context. The findings reveal two interconnected pathways of Islamization: a cultural-religious pathway associated with Javanese Islamic traditions and a political-structural pathway linked to the Maluku Sultanates. Rather than operating independently, these pathways interacted within wider maritime networks, enabling Bima's transformation into an Islamic sultanate. Religious belief provided legitimacy, while political authority institutionalized Islamic governance and shaped a distinctive Islamic identity. This study advances the historiography of Islamization in the Indonesian archipelago by proposing an interregional analytical framework that integrates religious and political dimensions. Despite the limited availability of primary sources, it offers a basis for future interdisciplinary research using newly discovered archival and manuscript evidence. The study demonstrates that the Islamization of Bima cannot be understood through a single regional influence. Instead, it highlights the interaction of interconnected interregional religious and political networks, providing a more comprehensive interpretation of the formation of Islamic authority and identity in the Bima Sultanate.